Governance and regulations' contemporary issues - Grima, Simon; Marano, Pierpaolo (Emerald Publishing Limited, 2018)
'Contemporary Issues in Economic and Financial Analysis 99' includes fourteen studies on contemporary issues within governance and regulations by authors invited from various universities and institutions. The chapters are a mix of discussion-based studies and empirical research studies aimed at understanding particular aspects of governance and regulations. Some refer to a particular country - specifically Malta, Indonesia, and India - and others are more generic and/or European-focused. These chapters include studies of the following: the challenges of corporate governance in small family-owned firms; a credit institution's perspective for managing conduct risk in the boardroom; the implications of the regulation and governance of financial advice in Europe for the retail financial advice sector and its consumers; the barriers to the development of Maltese cooperatives; corporate governance and cash holdings in Indian firms; whether good governance fosters trust in the government; the impact of takeover bids on European law and corporate governance; the developments and outcomes of the reform of the doctrine of "utmost good faith" in the UK; whether corporate decisions in Indonesia are a result of corporate governance requirements; earning management and audit reports; the European deposit insurance scheme; product intervention of supervisory authorities in financial services; the teaching of financial services regulation; how to link the human element to the risk management process, which is one of the internal control processes in governance of an organisation; and whether the transparency regime on the financial institutions market really works.
Includes index.
Keywords: Corporate governance.; Risk management.; Business & Economics -- Finance -- Financial Risk Management.; elektronické knihy; electronic books